Similar behaviors of natural ELF/VLF ionospheric emissions and transmitter signals over seismic Adriatic regions - M. Y. Boudjada; K. Schwingenschuh; H. K. Biernat; J. J. Berthelier; J. Blecki; M. Parrot; M. Stachel; Ö. Aydogar; G. Stangl; J. Weingrill (Natural Hazards and Earth System Sciences, 2008)
We report on the analysis of ELF/VLF emissions observed by the Instrument Champ Electrique (ICE) experiment onboard the DEMETER micro-satellite. We consider principally selected seismic events reported by Molchanov et al. (2006). These authors studied the VLF signals radiated by ground transmitters and received on board the DEMETER micro-satellite. They revealed a drop of the signals (scattering spot) connected with the occurrence of large earthquakes. In our investigations, we proceed to a spectral analysis of ICE observations with the aim to find if the natural ionospheric VLF/ELF emissions show, or not, a similar ''drop'' in the intensity as it is the case of the VLF transmitter signal. We combine our results with those of Molchanov et al. (2006), and we discuss the origin of such interesting ionospheric features in the frame of the investigation of the pre-seismic electromagnetic emissions. We show that the geomagnetic activity is a key parameter which could disturb the natural VLF ionospheric emissions, and also the transmitter signal. We find that it is not possible to conclude the presence, or not, of a preseismic effect when the Kp-index is higher than one.